CTLA‐4Ig (abatacept) balances bone anabolic effects of T cells and Wnt‐10b with antianabolic effects of osteoblastic sclerostin. Issue 1 (3rd March 2018) - Roser‐Page, Susanne; Vikulina, Tatyana; Weiss, Daiana; Habib, Mark M.; Beck, George R.; Pacifici, Roberto; Lane, Timothy F.; Weitzmann, M. Neale
Abstract: Activated lymphocytes promote inflammation and bone destruction in rheumatoid arthritis (RA), making T cells and B cells therapeutic targets. Indeed, pharmacological blockade of CD28 costimulation using CTLA‐4Ig (abatacept), approved for amelioration of RA, renders T cells dormant (anergic). CTLA‐4Ig also promotes bone accretion in healthy mice; surprisingly, however, this effect is driven exclusively through upregulation of bone formation, rather than anti‐inflammatory effects on resorption. In the study presented here, we utilized T cell receptor β gene and Wnt‐10b gene knockout mice to investigate the roles of T cells and Wnt‐10b in CTLA‐4Ig–induced bone anabolism. Ablation of either T cells or Wnt‐10b not only abolished CTLA‐4Ig–induced bone anabolism but also, paradoxically, suppressed bone formation leading to bone loss. Stalled bone formation was accompanied by bone marrow stromal cell expression of the Wnt pathway inhibitor sclerostin. Our data suggest that an immunoskeletal pivot may promote or suppress bone formation, depending on the net outcome of CTLA‐4Ig action directed independently on T cells and osteoblast‐linage cells that counter Wnt‐10b–induced bone anabolism, by secretion of sclerostin. While CTLA‐4Ig action is tipped in favor of bone formation under physiological conditions, pathological immunodeficiency may lead to suppressed bone formation and skeletal damage.